Analisis Dampak Kebisingan Lalu Lintas Udara Terhadap Nilai Rumah (Studi Pada Kawasan di Sekitar Bandar Udara Sultan Syarif Kasim II Pekanbaru) - Ritonga, M.Syarif Hidayatullah; Hidayati, Wahyu (Universitas Muhammadiyah Yogyakarta, 2011)
Â In the operational of aviation in Sultan Syarif Kasim II Pekanbaru Airport, an airplane machine can make some noise. The noise is sound that is not will in a place and time scale, it can make some disturbance that influence human freshness and health. Nevertheless in fact there are many settlements which developed in the noisy areas that are not in accordance with the regulations.The purpose of this study was to analyze the effect of air traffic noise in the area around the airport of Sultan Syarif Kasim II Pekanbaru to residential value, and to analyze other variables outside noise that affects the valueÂ of homes in the area around the airport. The variables used in this research is the building area, land area, number of bedrooms, number of bathrooms, distance from the house to the CBD, from the house to the airport, building structure and noise.By using multiple regression with least squares method (ordinary least square). The result show that the noise has a negative statistically significant against the value of the house. It can be concluded that noise can interfere with health and reduce comfort, which means reducing the benefits received by resident, there by reducing the value of the house.